PENGARUH MOTIVASI, PELATIHAN DAN PENGHARGAAN TERHADAP KINERJA PEGAWAI PADA LAPAS KELAS IIB BIREUEN - Farsi, Syuhada; Arief Syarifuddin, Evi (IndOmera, 2023)
This research was conducted on Class IIB Correctional Institution (LAPAS) employees of Bireuen Regency which aimed to analyze the effect of motivation, training and rewards on employee performance. The analytical method used is descriptive and verification analysis with multiple linear regression analysis. The results showed that (a) motivation has a significant effect on performance, (b) there is an effect of training on employee performance and (c) there is an effect of rewards on employee performance. Taken together, the factors of motivation, training and reward contribute positively to the performance of employees in Bireuen Class IIB Lapas